The relationship of non-verbal communication cues and student satisfaction / Sarah Sabir Ahmad …[et al.] - Ahmad, Sarah Sabir; Isahak Merican, Farah Merican; Ahmad, Intan Nazrenee; Md Zani, Rosliza (Research Management Institute, 2009)
Students’ satisfaction has become an essence of success in today’s highly competitive world. In service industry specifically the education industry, communication is vital to determine students’ satisfaction. Past researches indicated that, most meaning of conversational messages comes from non-verbal communication. Therefore, this study intended to examine the relationship of non-verbal communication cues to students’ satisfaction. A total of 330 respondents were sampled from all around UiTM Kedah. They were evaluated on their perception on lecturers’ non-verbal communication behavior that would lead to their satisfaction to the services provided. The results of the study illustrate that three of the non-verbal communication cues were significant and positively related to students’ satisfaction. Kinesics and paralanguage was rated as among the non-verbal communication cues that provided the most impact on students’ satisfaction. However, the result also indicated that there was no significant relationship between physical appearances of the lecturers to the students’ satisfaction. Overall, students’ in UiTM Kedah are fairly satisfied with the non-verbal communication cues of the lecturers. The present study caters for a wide spectrum of students and development professionals, especially those who are interested in non-verbal communication related issues. It is highly hoped that the information gleaned from the present study may assist all service employees specifically in understanding better, the importance of non-verbal communication and its effects on students’ satisfaction.